Bienestar psicológico y apoyo social en adultos mayores. - Renteria Samaniego, Arangely Yusibeth (2025)
The main objective of this research was to characterize psychological well-being and social support in older adults. The methodology used was bibliographic and descriptive. Scientific documentation extracted from databases such as Scopus, ProQuest, Redalyc, Dialnet, Pubmed, ScieLo, and Google Scholar was reviewed and analyzed. The quality of the articles chosen was validated by applying the CRF-QS (Critical Review Form-Quantitative Studies) instrument. The results obtained showed that psychological well-being is composed of the dimensions of environmental control, personal growth, life purpose, autonomy, self-acceptance, and positive relationships. It is an indicator of the levels of happiness that older adults can reach and vary depending on the socio-cultural and relational circumstances to which they are exposed, which will influence the generation of resources that will help the older adult cope with the various circumstances of the evolutionary stage in which he/she finds him/herself. It was evidenced that social support, which can be family, friends, or members of an organization to which he/she belongs, is important in the life of the older adult. It is important in the life of an older adult since it influences his mental health by being a protective factor against mental diseases such as depression and anxiety, among others, in addition to improving the quality of life because it avoids feelings of loneliness since he is aware that he can count on people around him when any difficulty of any kind arises.